RANCANG BANGUN WEBSITE WISATA GEOL DESA KABUPATEN LANGKAT - Amalia, Marini; Untung Suropati (Jurnal Nasional Teknologi Komputer, 2021)
This research is conducted with the aim of designing and building a tourist website in which it provides information on Wisata Geol in Pematang Serai Village. This research is based on the basis of the needs of containers as promotional media also provides information quickly and accurately, because the delivery of information on the current Wisata Geol is still done manually which is considered still not effective. In addition, this information system makes it easy to visitors to book ticket reservations via website previosly made by hand through celluler phone calls. With this information system it will make it easier for the administration of the misata to file a visitor’s report. These web tours use Mysql Database and use PHP Programming language and employ multiple support applications such as a Balsamiq Mockup for a design and CSS display for a website page view